Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Kendaraan Bermotor Honda Scoopy - Ahmad Dwi Nurdiyanto (Universitas Ngudi Waluyo, 2022)
The purpose of this study was to determine and analyze the effect of product quality on purchasing decisions for Honda Scoopy Motorized Vehicles and to determine the effect of Brand Image on Purchase Decisions for Honda Scoopy Motor Vehicles. The population in this study was 60 respondents. This study uses the Census Sampling method. The results can be concluded that product quality has no positive and insignificant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions.